The Impact of Gadgets on Moral Values during the Covid-19 Pandemic in Early Childhood - Nurhayati Nurhayati; I Putu Suwika; Nurhidaya Ahmad (STAI Hubbulwathan Duri, 2023)
This research is motivated by initial observation data and initial interviews showing childsren's moral values have not developed properly. This study aims to determine the impact gadget on children's moral values during the covid-19 pandemic. This research uses descriptive research with qualitative research methods. Data collection techniques through observation, questionnaires, interviews and documentation. The data analysis technique used percentage and descriptive techniques to obtain qualitative data. Based on the results of the average percentage recapitulation the first week to the third week. In the aspect of respecting parents, the highest percentage is in the Beginning to Develop category of 46.6%, while the lowest percentage is in the Undeveloped category of 6.7%. In the discipline aspect, the highest percentage is in the Starting to Develop category at 46.7%, while the lowest percentage is in the Very Good Developing category at 4.4%. In the polite aspect, the highest percentage is in the Beginning to Develop category at 51.1%, while the lowest percentage is in the Undeveloped category at 4.4%. In the aspect of good behavior, the highest percentage is in the Beginning to Develop category at 60%, while the lowest percentage is in the Undeveloped category at 2.2%. The percentage of time / duration of gadget in the